Pengaruh Pengawasan Terhadap Sarana Publik Trotoar oleh Dinas Perhubungan di Kecamatan Wenang Kota Manado - Sthumbelina A.A. Tabisi; FLORENCE DAICY LENGKONG; VERY LONDA (JURNAL ADMINISTRASI PUBLIK, 2023)
This research was conducted with the aim of knowing the effect of supervision from the service on public sidewalk facilities in Wenang District in the study of public administration. This research uses a quantitative method by using the dimensions of setting measuring instruments or standards, carrying out assessment or evaluation actions, carrying out corrective actions for monitoring variables, having the right dimensions, appropriate structure and slope, stairs that are friendly for the disabled, comfortable, and safe, and using utility canals or drainage manhole covers for the variable sidewalk public facilities. This study used simple linear regression analysis with data collected using instruments in the form of questionnaires or questionnaires with a Likert scale. The results of the research under investigation show that supervision from the Department of Transportation has a positive effect on public sidewalk facilities in Wenang District. Government oversight in terms of setting measuring instruments or standards, carrying out assessment or evaluation actions, and taking corrective actions is in accordance with procedures or rules, but the quality of existing processes is still not optimal. Keywords: Monitoring, Public Facilities, Sidewalk